JAMINAN KESEHATAN DALAM HAK KONSTITUSIONAL BAGI PEKERJA MIGRAN INDONESIA DALAM KONSTRUKSI NEGARA KESEJAHTERAAN - AGUNG, Asri Agung Putra; Jatmiko, Ludfie Jatmiko Setyo Poerwoko (The Prosecutor Law Review, 2023)
In Indonesia, the preamble and body of the 1945 Constitution is a strong ideological basis that this country adheres to the welfare state. So that the legal basis for providing social security (health) for every citizen, Both those who are in the country and abroad should have the same opportunity to get social security, especially when we talk about Indonesian Migrant Workers who contribute large amounts of foreign exchange to Indonesia, we should no longer hear about Indonesian Migrant Workers who do not get Health Insurance. The responsibility for protecting and fulfilling these constitutional rights rests with the state and should be guaranteed by law as a consequence of the realization of a welfare state. This is as mandated by Article 28 I paragraph (4) and paragraph (5) of the 1945 Constitution of the Republic of Indonesia which states that, protection, promotion, enforcement and fulfillment of human rights is the responsibility of the state, especially the government and to uphold and protect human rights in accordance with the principles of a democratic rule of law